Factors Affecting Systolic Blood Pressure In Police Personnel - Regita Irsti Ananda; Miratul Haya; Kusdalinah Kusdalinah (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
Blood pressure is a condition where a person's blood pressure is high because of the narrowing of the arteries so that the pressure increases. Age is life time. Sodium is the main cation in extracellular fluid. Smoking is one of the factors associated with hypertension, and RLPP has a lot of fat in the stomach. The purpose of this study was to determine the factors that influence systolic blood pressure in police officers. The design of this study was observational analytic with cross sectional approach. This study is a member of the Police in Central Bengkulu Police with a random sampling technique and obtained 59 samples. The design of this study was observational analytic with cross sectional approach. The population in this study were 59 members of the Police in Bengkulu Tengah Police Station, with a random sampling technique. This study used univariate and bivariate analysis, for univariate using frequency test the results showed an average blood pressure of 122 mmHg, an average age of 36 years, an average RLPP of 0.15 and an average sodium consumption of 1114 mg. Whereas for bivariate using chi square test found no relationship between systolic blood pressure and age, there was a relationship between systolic blood pressure and smoking history (OR = 10,467; p <0,0005), there was a relationship between systolic blood pressure with RLPP (OR = 178; p <0,0005), there is a relationship between systolic blood pressure and sodium consumption (OR = 0.351; p <0,0005) in police officers at Bengkulu Central Police Station in 2020. It is expected that respondents will be able to receive information so that preventive efforts can be made against blood pressure diseases in the future.